Preliminary study on spermatological characteristics of frizzled Hungarian ganders - Almási, Anita; Varga, Ákos; Barna, Judit; Bogenfürst, Ferenc; Molnár, Marcell (Acta Agraria Kaposváriensis, 2002)
One of the most significant results in the poultry breeding researches of the 20th century was the elaboration of the technique of artificial insemination. By its help higher fertility rate and reduced reproduction problems can be reached in the different poultry species. Although, the low fecundity rate (62–63%), the susceptibility to monogamy, asynchronism of the sexual activity in the two sexes, the hygienic problems (phallus- disease, infection during mating) and the seasonality indicate the need of the routinely application of the artificial insemination in the goose breeding, in the practice it is achieved only ad hoc. Contrary to the generally used farm types with the frizzled goose there were no examinations focused on the parameters of male reproduction. The aim of our investigations was to determine the quantitative and qualitative parameters of frizzled gander semen (average volume, concentration, motility, morphology, frequency of abnormalities, viable: dead cell ratio) ensuring a basis for the long and short term storage of gander semen and the ex situ gene conservation.
Keywords: spermatological characteristics; frizzled Hungarian ganders